Edukasi Penggunaan QRIS dalam Perspektif Fiqih Muamalah: Penguatan Transaksi Digital Halal dan Bebas Riba bagi Pelaku UMKM di Kota Baubau - Abdul Kahar Syrarifuddin; La Jusu; La Hanuddin; Jufri; Nur Aribah; Ulfa Ramadhani; Ahmad Saiful (LPPM UNINUS, 2025)
This community service program aimed to strengthen QRIS-based digital payment literacy among MSME (UMKM) actors in Baubau City through a fiqh al-muʿāmalāt perspective, enabling cashless transactions that are halal, transparent, and free from ribā. The program was initiated in response to the rapid expansion of QRIS usage in the retail and MSME sector, which has not been consistently matched by adequate understanding of service-related contracts (ʿaqd), ujrah (service fees), gharar prevention, and dispute-handling procedures such as complaints and refunds. A participatory implementative approach was employed, consisting of: (1) a needs assessment through field observation and guided interviews; (2) interactive education sessions combining QRIS operational concepts with key muʿāmalāt principles; (3) hands-on training and case-based simulations covering payment verification, transaction records, settlement processes, and common errors; (4) the development of a “Sharia-Compliant QRIS Transaction SOP” tailored to MSME contexts; and (5) mentoring, monitoring, and evaluation using pre post tests, observation checklists, and participant feedback. The results indicate improved participant comprehension of QRIS mechanisms and a clearer conceptual distinction between riba and permissible ujrah when fees are disclosed, agreed upon, and linked to legitimate services. Participants also demonstrated stronger practical competence in conducting transactions independently, storing transaction evidence, maintaining simple daily records, and managing frequent issues such as incorrect amounts, failed payments, and refunds in a fair and orderly manner. Key outputs included a concise module, a checklist infographic, and an operational SOP to support sustainability. Conceptually, the findings highlight the importance of value compatibility with Islamic commercial jurisprudence in accelerating digital payment adoption among MSMEs. Overall, the program contributes to enhanced consumer trust, better transaction governance, and aligns with inclusive economic empowerment and the SDGs.